2019
DOI: 10.1002/cncy.22147
|View full text |Cite
|
Sign up to set email alerts
|

Needle track seeding in renal mass biopsies

Abstract: A review and analysis of the literature demonstrates that needle track seeding in renal mass biopsy has been reported 16 times. This complication occurs almost exclusively among patients with papillary renal cell carcinoma. The incidence is associated with multiple punctures of the mass, the use of core needles of ≥20 gauge, and lack of a coaxial sheath. Needle tract seeding may be associated with tumor upstaging and a worse prognosis. Fine-needle aspiration has a significantly lower rate of needle track seedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Some studies observed that PRCC tend to exhibit incomplete or absent peritumoral pseudo-capsule more frequently than CCRCC, facilitating tumor invasion into the perinephric fat [ 23 ]. Other hypotheses for higher rate of needle tract tumor seeding in PRCC include the friable nature of the tumor facilitating tumor cell adherence to the needle, higher frequency of exophytic growth allowing tumor seeding more often in the extrarenal space, as well as possible higher chance of tumor cell survival when explanted into the needle tract [ 17 ]. Nevertheless, the exact reasons for the differences in the frequencies of biopsy needle tract tumor seeding among various pathologic types of renal tumors need further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies observed that PRCC tend to exhibit incomplete or absent peritumoral pseudo-capsule more frequently than CCRCC, facilitating tumor invasion into the perinephric fat [ 23 ]. Other hypotheses for higher rate of needle tract tumor seeding in PRCC include the friable nature of the tumor facilitating tumor cell adherence to the needle, higher frequency of exophytic growth allowing tumor seeding more often in the extrarenal space, as well as possible higher chance of tumor cell survival when explanted into the needle tract [ 17 ]. Nevertheless, the exact reasons for the differences in the frequencies of biopsy needle tract tumor seeding among various pathologic types of renal tumors need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a handful of case reports and a small case series have been published [8,[11][12][13][14][15][16]. However, the frequency and clinical significance of biopsy-associated tumor seeding remains largely controversial due at least in part to lack of systemic review, histological analysis and follow up data in early studies [9,10,17]. In recent years, a few studies re-visited the phenomenon of tumor seeding along core needle biopsy tract in renal cell carcinomas and challenged the previously acknowledged rarity of needle tract tumor seeding following renal tumor biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…However, cases with involvement beyond perirenal tissue have been reported with the use of smaller needles, including a 23‐gauge needle, as well as with coaxial sheaths; therefore, BTS still occurs with needles of different sizes, with or without a coaxial sheath, and may account for the cases of BTS‐P in our institution, given that we use an 18‐gauge coaxial needle 16,19 . No cases of BTS have been identified when needles of <20 gauge and a coaxial sheath have been used, 26 and it seems that using both may eliminate the risk. However, because of insufficient data and the undetermined clinical significance of BTS beyond the adjacent tissues of the kidney, it is still unclear how to appropriately stage these tumours; these are aspects of BTS that were not addressed in this study.…”
Section: Discussionmentioning
confidence: 85%
“…Herein, we discuss only the significance of BTS‐P, as none of the cases in our cohort had involvement beyond the perinephric tissue. Although BTS is rare, its presence has been associated with the use of needles of ≥20 gauge, the lack of a coaxial sheath, and multiple passes of the renal mass 26,27 . However, cases with involvement beyond perirenal tissue have been reported with the use of smaller needles, including a 23‐gauge needle, as well as with coaxial sheaths; therefore, BTS still occurs with needles of different sizes, with or without a coaxial sheath, and may account for the cases of BTS‐P in our institution, given that we use an 18‐gauge coaxial needle 16,19 .…”
Section: Discussionmentioning
confidence: 94%
“…4 These data also expand the list of benign renal lesions (oncocytoma, cystic nephroma, angiomyolipoma, and papillary adenoma [given the appropriate size]) that in at least some cases can be recognized on cytologic material alone. In many cases, these lesions can be confirmed with immunohistochemistry (IHC) performed on core needle biopsy, though large core needle biopsy of renal lesions has its drawbacks (most notably bleeding and needle track seeding 5 ).…”
mentioning
confidence: 99%